RANCANG BANGUN APLIKASI PEMANDU WISATA MUSEUM SUMBAWA BERBASIS ANDROID DENGAN MEMANFAATKAN QUICK RESPONSE CODE (QR CODE) - Muhammad Habibullah; Yudi Mulyanto; Nora Dery Sofya (Jurnal Informatika Teknologi dan Sains, 2020)
The Sumbawa Regional Museum is a storage and exhibition of Sumbawa Regency historic objects. This research aims to design and build application that can be used to manage the addition, updating or deletion of data objects from the Sumbawa Regional Museum collection and can be used by visitors of the Sumbawa Regional Museum to view information about museum collection objects by scanning the Quick Response Code (QR Code) which has been pasted on museum collection objects. Researcher built an application that can run on the android and web platforms, developed using the Java and PHP programming language, and using MySQL as a database. The software development method uses Waterfall Model until the software testing stage using the blackbox method. Data collection techniques in research using interview and documentation. The results of this research are museum tour guide application and museum collection data management